Changing pleural fluid triglyceride levels in cirrhotic chylothorax. Issue 3 (12th February 2022) - Chan, Ka Pang; Yip, Wing Ho; Chan, Tina Yee Ching; Law, Chun‐Yiu
Abstract: Chylothorax is an uncommon disease entity, but it occasionally poses a diagnostic challenge to physicians. Pleural fluid triglyceride level has been advocated as a screening test to diagnose chylothorax. However, its level can be depressed if there is an additional pathology driving the process of pleural fluid production. We report a case of high‐volume pleural fluid output due to dual pathologies, cirrhotic hydrothorax and chylothorax, causing an initial failure to diagnose chylothorax due to low pleural fluid triglyceride level. The fluid triglyceride levels were unmasked after the treatment for underlying portal hypertension. These findings were further substantiated by positive lipoprotein electrophoresis for chylomicron. In this patient, lipoprotein electrophoresis of his pleural fluid specimen helps distinguish chylothorax as a second pathology amidst the underlying cirrhotic hydrothorax. Abstract : This case report illustrated changing pleural fluid triglyceride levels during the treatment for hepatic hydrothorax and underlying chylothorax. The diagnosis was finally established by confirming the presence of chylomicron using lipoprotein electrophoresis.